Modelling the HIV epidemic among MSM in the United Kingdom. (28th January 2015) - Punyacharoensin, Narat; Edmunds, William John; De Angelis, Daniela; Delpech, Valerie; Hart, Graham; Elford, Jonathan; Brown, Alison; Gill, Noel; White, Richard G.
<x xml:space="preserve">Abstract</x> Objectives: HIV is a major public health problem among MSM in the United Kingdom with around 2400 new infections annually. We quantified the contribution of biological and behavioural factors. Design: Modelling study. Methods: A partnership-based model of HIV transmission among UK MSM aged 15–64 years was developed and calibrated to time series HIV prevalence. The calibration was validated using multiple surveillance datasets. Population-attributable fractions were used to estimate the contribution of behavioural and biological factors to HIV transmission over the period 2001–2002, 2014–2015, and 2019–2020. Results: The contribution of most biological and behavioural factors was relatively constant over time, with the key group sustaining HIV transmission being higher-sexual activity MSM aged below 35 years living with undiagnosed HIV. The effect of primary HIV infection was relatively small with 2014–2015 population-attributable fraction of 10% (3–28%) in comparison with other subsequent asymptomatic stages. Diagnosed men who were not on antiretroviral therapy (ART) currently contributed 26% (14–39%) of net infections, whereas ART-treated MSM accounted for 17% (10–24%). A considerable number of new infections are also likely to occur within long-term relationships. Conclusion: The majority of the new HIV infections among MSM in the United Kingdom during 2001–2020 is expected to be accounted for by a small group of younger and highly sexually active individuals, living with undiagnosed HIV in the asymptomatic stage. Bringing this group into HIV/AIDS care by improving testing uptake is a vital step for preventing onward transmission and will determine the success of using ART as prevention.